Safety, efficacy and changing trends in endoscopic ablation for dysplastic Barrett's esophagus in Poland: a long-term multicenter retrospective analysis - Romanczyk, Marcin; Klimkowski, Robert; Kukla, Michal; Pilonis, Nastazja D; Romanczyk, Tomasz; Gorecka, Magda; Lesinska, Magdalena; Wronska, Ewa; Regula, Jaroslaw; Kaminski, Michal F; Januszewicz, Wladyslaw (Polskie archiwum medycyny wewne̦trznej, 2025)
Endoscopic ablation is the mainstay treatment for dysplastic Barrett's esophagus (BE), of which radiofrequency ablation (RFA) and argon plasma coagulation (APC) are the most widely available options.INTRODUCTIONEndoscopic ablation is the mainstay treatment for dysplastic Barrett's esophagus (BE), of which radiofrequency ablation (RFA) and argon plasma coagulation (APC) are the most widely available options.We aimed to analyze the safety and outcomes of endoscopic ablation for BE within Polish centers.OBJECTIVESWe aimed to analyze the safety and outcomes of endoscopic ablation for BE within Polish centers.We retrospectively analyzed data from three high-volume endoscopy units between 2002-2024. We included adult patients with confirmed BE who received ≥1 ablation session with either conventional/hybrid APC (APC/h-APC) or RFA, followed by ≥1 endoscopic follow-up. The outcomes included: the rate of complete remission of intestinal metaplasia (CR-IM) and dysplasia (CR-D), and adverse events rate (AEs). Risk factors for treatment failure were analyzed using a multivariable logistic regression model.PATIENTS AND METHODSWe retrospectively analyzed data from three high-volume endoscopy units between 2002-2024. We included adult patients with confirmed BE who received ≥1 ablation session with either conventional/hybrid APC (APC/h-APC) or RFA, followed by ≥1 endoscopic follow-up. The outcomes included: the rate of complete remission of intestinal metaplasia (CR-IM) and dysplasia (CR-D), and adverse events rate (AEs). Risk factors for treatment failure were analyzed using a multivariable logistic regression model.We analyzed data from 191 patients, of which 160 were included (mean age 59.4[10.8] years; 79.4% males). Overall, the CR-IM and CR-D rates were 80.0% and 93.8%, respectively. We reported 49 minor AEs(30.6%), and 9 major AEs (5.6%), including 7 esophageal strictures (4.4%). In the early 2000s, APC was the only available ablation modality. However, since 2008, it has been gradually replaced by RFA. Notably, RFA was used for more severe BE cases and carried a higher risk of failed treatment than APC/h-APC (odds ratio [OR] 7.48,P=0.001). Other risk factors for treatment failure included the BE-length (OR 1.3,P=0.002) and diabetes (OR 7.48,P<0.001).RESULTSWe analyzed data from 191 patients, of which 160 were included (mean age 59.4[10.8] years; 79.4% males). Overall, the CR-IM and CR-D rates were 80.0% and 93.8%, respectively. We reported 49 minor AEs(30.6%), and 9 major AEs (5.6%), including 7 esophageal strictures (4.4%). In the early 2000s, APC was the only available ablation modality. However, since 2008, it has been gradually replaced by RFA. Notably, RFA was used for more severe BE cases and carried a higher risk of failed treatment than APC/h-APC (odds ratio [OR] 7.48,P=0.001). Other risk factors for treatment failure included the BE-length (OR 1.3,P=0.002) and diabetes (OR 7.48,P<0.001).Endoscopic ablation for BE is safely and effectively provided in Poland within a few expert centers. Patients with diabetes and long-segment BE are at increased risk for treatment failure.CONCLUSIONSEndoscopic ablation for BE is safely and effectively provided in Poland within a few expert centers. Patients with diabetes and long-segment BE are at increased risk for treatment failure.